2014
DOI: 10.1002/jssc.201400186
|View full text |Cite
|
Sign up to set email alerts
|

A quick, easy, cheap, effective, rugged, and safe method for the simultaneous detection of four triazolone herbicides in cereals combined with ultrahigh performance liquid chromatography with tandem mass spectrometry

Abstract: This paper describes a novel, rapid, and sensitive analytical method for monitoring four triazolone herbicides in cereals (wheat, rice, corn, and soybean), using a quick, easy, cheap, effective, rugged, and safe sample extraction procedure followed by ultrahigh performance liquid chromatography coupled with tandem mass spectrometry. The four triazolone herbicides (amicarbazone, carfentrazone-ethyl, sulfentrazone, and thiencarbazone-methyl) were extracted using acidified acetonitrile (containing 1% v/v formic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The principle applied was extraction with acetonitrile combined with solid‐phase extraction to achieve rapid extraction and remove impurities . Based on the existing methods , acetonitrile was selected as the extraction solvent. To obtain better recovery and purification, five types of sorbent combinations (Sorbent 1: 100 mg PSA; Sorbent 2: 50 mg C18; Sorbent 3: 100 mg GCB; Sorbent 4: 50 mg PSA + 50 mg C18; Sorbent 5: 50 mg PSA + 50 mg GCB) were investigated at the spiking level of 100 μg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…The principle applied was extraction with acetonitrile combined with solid‐phase extraction to achieve rapid extraction and remove impurities . Based on the existing methods , acetonitrile was selected as the extraction solvent. To obtain better recovery and purification, five types of sorbent combinations (Sorbent 1: 100 mg PSA; Sorbent 2: 50 mg C18; Sorbent 3: 100 mg GCB; Sorbent 4: 50 mg PSA + 50 mg C18; Sorbent 5: 50 mg PSA + 50 mg GCB) were investigated at the spiking level of 100 μg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…QuEChERS greatly simplifies the sample pretreatment procedure and reduces total analysis time. From previous literature, acceptable precision and accuracy were generally obtained . Belemguer et al.…”
Section: Introductionmentioning
confidence: 76%
“…In this study, the Waters Acquity UPLC BEH C18 column (2.1 × 50 mm, 1.7 μm particle size) was first selected. In the positive ESI mode, the use of an acidic mobile phase is conducive to protonate the target compound and can improve the response and peak shape . Therefore, we compared water to 0.2% v/v FA aqueous solution for the aqueous phase, and found that the 0.2% v/v FA aqueous solution was better than water for improving response.…”
Section: Resultsmentioning
confidence: 99%